Large Meteorite Impacts and Planetary Evolution; II 1999
DOI: 10.1130/0-8137-2339-6.61
|View full text |Cite
|
Sign up to set email alerts
|

Morokweng impact structure, South Africa: Geologic, petrographic, and isotopic results, and implications for the size of the structure

Abstract: A large impact structure has been identified around Morokweng in the Northwest Province of South Africa. The central aeromagnetic anomaly of this structure is caused by a ~30-km-wide melt body. Textural, mineralogical, and chemical analyses of many drill-core samples of this melt rock are reported. Shock metamorphism in granitoids drilled below the melt body confirms the origin of this melt rock by impact melting. The age of the Morokweng impact melt rock is well-constrained at 145 Ma from single zircon U-Pb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In addition, impact melt injected into the crater floor may macroscopically closely resemble some types of pseudotachylitic breccia (e.g., as diagnosed in the Morokweng impact structure - Reimold et al, 1999). Lambert (1981) provided a detailed report of very different types of melt-bearing or cataclastic breccias occurring within the crater floor rocks of the Rochechouart impact structure in France.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, impact melt injected into the crater floor may macroscopically closely resemble some types of pseudotachylitic breccia (e.g., as diagnosed in the Morokweng impact structure - Reimold et al, 1999). Lambert (1981) provided a detailed report of very different types of melt-bearing or cataclastic breccias occurring within the crater floor rocks of the Rochechouart impact structure in France.…”
Section: Introductionmentioning
confidence: 99%
“…Gibson & Reimold 2008;Reimold & Koeberl 2014). Reimold et al (1999) demonstrated in a detailed petrographic and chemical investigation of dyke breccias from the crater floor of the large Morokweng impact structure in South Africa (Reimold & Koeberl 2014) that both melt-bearing impact breccias and impact-generated cataclasite (monomict lithic impact breccia) were present. This represents a typical example that a range of clast-based or melt-bearing breccias may occur in such settings and megascopically closely resemble friction melt.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of this possible impact structure was estimated at 120 km from interpretation of regional geophysical data, which would make Woodleigh one of the 5 largest impact structures (after Vredefort, Sudbury, Chicxulub) known from the terrestrial impact cratering record (compare Grieve 1991; Grieve et al 1995). Mory et al (2000a) also placed the Morokweng impact structure, South Africa, in a similar size category, but initial indications of a >100-200 km diameter of this structure (e.g., Reimold et al 1999) have been refined to about 70 or 80 km based on more recent studies (e.g., Henkel et al 2002;Reimold et al 2002).…”
Section: Introductionmentioning
confidence: 99%